2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907681
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for robot inclusive spaces: A case study with Roomba

Abstract: Abstract-Research focus on service robots that deals with applications related to healthcare, logistics, residential, search and rescue are gaining significant momentum in the recent years. Their social and economic relevance is more than evident. Yet, while much has been researched about "designing robots" focusing on sensing, actuation, mobility and control of service robots, little work has been done on "design for robots" that looks at designing preferred artefacts or environments for such robots. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Recently Mohan et al proposed a new design perspective, called robot-inclusive space design, to designing interior space for service robots [38,39], which suggests a "design for robot" approach to complement the conventional "designing robot" approach with an objective of overcoming the multiple research challenges identified by roboticists. The approach suggests designing and adapting spaces and its component variables such as lighting, furniture, flooring, doors, and walls to be suitable for the deployment of robots, a perspective that departs from the usual approach of optimizing the components technologies such as perception, action, and cognition without any inclusive adaptations to the operating environments.…”
Section: Robot-inclusivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently Mohan et al proposed a new design perspective, called robot-inclusive space design, to designing interior space for service robots [38,39], which suggests a "design for robot" approach to complement the conventional "designing robot" approach with an objective of overcoming the multiple research challenges identified by roboticists. The approach suggests designing and adapting spaces and its component variables such as lighting, furniture, flooring, doors, and walls to be suitable for the deployment of robots, a perspective that departs from the usual approach of optimizing the components technologies such as perception, action, and cognition without any inclusive adaptations to the operating environments.…”
Section: Robot-inclusivenessmentioning
confidence: 99%
“…The approach suggests designing and adapting spaces to be suitable for the deployment of robots, a perspective that departs from the usual bottom-up approach followed in robotics where robots must fit the existing environments. The design criteria are observability, accessibility, manipulability, activity, and safety for environments involving sociable robots living and working alongside humans [11,39]. A well designed robot-friendly environment would allow for easy robot perception of obstacles, landmarks and artifacts of interests (observability).…”
Section: Design Criteria and Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, some studies have identified a link between robot and environment [14][15][16]. Tan, Mohan [16] has emphasized the importance of five factors of robot-friendly environment, which comprise observability, manipulability, activity, and safety.…”
Section: Living Environmentmentioning
confidence: 99%